Epidermal growth factor receptor (EGFR) in lung cancer: an overview and update - Bethune, Gillian; Bethune, Drew; Ridgway, Neale; Xu, Zhaolin (Journal of Thoracic Disease; Vol 2, No 1 (March 11, 2010): Journal of Thoracic Disease, 2011)
Epidermal growth factor receptor is a trans-membrane glycoprotein with an extracellular epidermal growth factor binding domain and an intracellular tyrosine kinase domain that regulates signaling pathways to control cellular proliferation. Epidermal growth factor receptor binding to its ligand results in autophosphorylation by intrinsic tyrosine/kinase activity, triggering several signal transduction cascades. Constitutive or sustained activation of these sequences of downstream targets is thought to yield more aggressive tumor phenotypes. Mutations in epidermal growth factor receptor have been discovered in association with some lung cancers. Lung adenocarcinomas with mutated epidermal growth factor receptor have significant responses to tyrosine kinase inhibitors, although for unselected patients it does not appear to have a survival benefit. However, in a subset of patients (non-smoking Asian women with adenocarcinoma, particularly with a bronchioloalveolar carcinoma), there appears to be a significant survival advantage. Both EGFR mutation and gene amplification status may be important in determining which tumors will respond to tyrosine kinase inhibitors.